Pointless atheism - Hendricks, Perry (Religious studies, 2025)
Say theism is the view that an omnipotent, omniscient, perfectly loving, and perfectly good being exists. And say pointless atheism occurs just in case there's an atheist who isn't resistant to belief in God, and no greater good comes about on account of this atheist's non-belief. In this article, I show that if two prominent views about evil and divine hiddenness are accepted, theism is compatible with pointless atheism - a result hitherto unnoticed. Furthermore, not only is theism compatible with pointless atheism, it entails pointless atheism. This is significant because many objections to the argument from divine hiddenness have tried to show that all instances of non-resistant atheism are required for a greater good. But if I'm right, given theism, there need not be a point to non-resistant atheism. Indeed, we should expect there to be pointless atheism.